2022
DOI: 10.1021/jacs.2c05834
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Above-Room-Temperature Superconductivity in Lanthanide/Actinide Extreme Superhydrides

Abstract: Achieving room-temperature superconductivity has been an enduring scientific pursuit driven by broad fundamental interest and enticing potential applications. The recent discovery of high-pressure clathrate superhydride LaH 10 with superconducting critical temperatures (T c ) of 250−260 K made it tantalizingly close to realizing this long-sought goal. Here, we report a remarkable finding based on an advanced crystal structure search method of a new class of extremely hydrogen-rich clathrate superhydride MH 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 55 publications
1
40
0
Order By: Relevance
“…The structural prediction is based on a global minimum search of the free energy surfaces calculated via ab initio density functional theory (DFT) total-energy calculation and through the particle swarm optimization algorithm implemented in the CALYPSO method. The key feature of this methodology is its capability of predicting the ground-state stable structures of materials with only the knowledge of chemical composition under ambient or given external conditions (e.g., pressure). The candidate structure was predicted at 0, 20, 40, 60, and 80 GPa using a simulation cell comprising two and four formula units. The ab initio structural relaxations and electronic properties were examined in the framework of DFT as implemented in the Vienna ab initio simulation package (VASP) code .…”
Section: Methodsmentioning
confidence: 99%
“…The structural prediction is based on a global minimum search of the free energy surfaces calculated via ab initio density functional theory (DFT) total-energy calculation and through the particle swarm optimization algorithm implemented in the CALYPSO method. The key feature of this methodology is its capability of predicting the ground-state stable structures of materials with only the knowledge of chemical composition under ambient or given external conditions (e.g., pressure). The candidate structure was predicted at 0, 20, 40, 60, and 80 GPa using a simulation cell comprising two and four formula units. The ab initio structural relaxations and electronic properties were examined in the framework of DFT as implemented in the Vienna ab initio simulation package (VASP) code .…”
Section: Methodsmentioning
confidence: 99%
“…Nearly room temperature superconductivity with a T c of ∼203 K in H 3 S 13 and T c ∼250 K in LaH 10 14 , 15 was reached at pressures of ∼150–170 GPa. The latest theoretical calculations predict T c s exceeding room temperature: T c ∼330 K in CeH 18 16 , and ∼470 K for Li 2 MgH 16 17 at higher pressures of ∼300–500 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been theoretically reported that many rare-earth and actinide elements can hold a large amount of nonmolecular hydrogen under high pressure, forming a series of clathrate compounds MH 18 (M: rare-earth/actinide metals) of which CeH 18 hosts a high T c of 329 K at 350 GPa. 36 As discussed above, valence electrons tend to accumulate in interstitial regions in the compressed K lattice, which makes K a promising metal element capable of stabilizing higher atomic hydrogen under high pressures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, many superhydrides exist in the form of hydrogen molecular units after the hydrogen content increases, and generally do not have excellent superconductivity, such as MgH 16 , SrH 22 , etc. The challenge now is to find a suitable metal element that can hold higher hydrogen content in the state close to the atomic hydrogen, and the resulting superhydride may exhibit higher T c . Recently, it has been theoretically reported that many rare-earth and actinide elements can hold a large amount of nonmolecular hydrogen under high pressure, forming a series of clathrate compounds MH 18 (M: rare-earth/actinide metals) of which CeH 18 hosts a high T c of 329 K at 350 GPa . As discussed above, valence electrons tend to accumulate in interstitial regions in the compressed K lattice, which makes K a promising metal element capable of stabilizing higher atomic hydrogen under high pressures.…”
Section: Introductionmentioning
confidence: 99%